Preliminary Report of the Archaeofauna at Skálholt, Iceland - Hambrecht, George (NABO and CUNY) (the Digital Archaeological Record)
This report presents results of a preliminary analysis of the archaeofauna at the Episcopal farm of Skálholt, Arnessyslá, southern Iceland. This report presents the preliminary analysis of group 634. Group 634 was a 3X5 meter trench oriented lengthwise north to south opened up on June 28th of 2004 by Birna Lárusdóttir. Further excavation of this group was conducted by George Hambrecht during June of 2005, and a 1x3 meter extension was opened up off of the north end of the initial trench. This work was conducted in conjunction with the FSI excavations of the early modern phases of Skálholt. A total of 11,176 bone fragments were recovered from group 634. An analysis of faunal remains from other contexts is on-going. Previous reports (Hambrecht et al. 2004, 2005) have covered the analysis of a large midden of cattle bones (unit 454) as well as some other finished contexts. Total number of bone fragments analyzed from the Skálholt archaeofauna to date is 48,674. All sediments were dry sieved through 4mm mesh to standardize recovery of bones following usual NABO recommendations.